UPAYA MENINGKATKAN MOTIVASI BELAJAR IPAS MENGGUNAKAN GAME TEBAK GAMBAR PADA PESERTA DIDIK KELAS VI SDN 066050 MEDAN - Ledy Chintia Marbun; Feri Haryati; Roma Ulinta Saragih (STKIP Subang, 2024)
This research aims to increase the science and science learning motivation of class VI students. This research uses a qualitative approach. The types of Classroom Action Research (PTK) Kemmis & Mc Tggart model are planning, action, observation and reflection. The subjects of this research were all class VI students at SDN 060650 Medan, totaling 21 students, consisting of 7 girls and 14 boys. The focus of this research is to increase students' learning motivation. The results of this research show that the picture guessing game can increase student motivation. Judging from the implementation of actions in learning from initial observations, it was found that the average level of student motivation in cycle I was 66.04 complete for 7 students or 33.33%, and not yet complete. there were 14 students or 66.66%. experienced an increase in cycle II with an average of 84.37, there were 18 students or 87.5% complete and 3 students or 12.5% ​​had not yet completed, thus there was an increase in student learning motivation. Student learning motivation in cycle II has met the success indicators because ≥ 75% have reached the KKM.